# Calculus

Let f(x) = -2/((5+3x)^4)

Determine f'(x) using the chain role.

Can someone please do this step by step and explain?

1. 👍 0
2. 👎 0
3. 👁 140
1. first change it to
f(x) = -2(5+3x)^-4

f'(x) = -8(5+3x)^-5 (3)
= -24(5+3x)^-5 or -24/((5+3x)^5)

1. 👍 0
2. 👎 0

## Similar Questions

1. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,

2. ### math

Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

3. ### physics 11

Timmy twirls a dead rat (mass = 2 kg) attached to a rusty chain (length = 1m) in a vertical circle. With what velocity should Timmy rotate the rodent so that the chain just goes slack (no force in the chain) at the top? pls answer

4. ### Science

which term best describes the role carbon plays in the structure of compounds present in living things? A- a somewhat important role B- a fundamental role C- a minimal role I think it B.

2. ### Calculus

(i) A 20m chain with a mass-density of 3kg/m (coiled on the ground). How much work is performed lifting the chain so that it is fully extended (and one end touches the ground)? (ii) How much work is performed to lift 1/4 of the

3. ### calculus

a 50 m long chain hangs vertically from a cylinder attached to a winch. assume there is no friction in the system and that the chain has a density of 5 kg/m. how much work is required to wind the entire chain onto the cylinder

4. ### ALGEBRA HELP

When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

1. ### math

An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and why? Step 1,